2008
DOI: 10.1063/1.2945880
|View full text |Cite
|
Sign up to set email alerts
|

Ion irradiation-induced local structural changes in amorphous Ge2Sb2Te5 thin film

Abstract: The crystallization kinetics of as-deposited and ion implanted amorphous Ge2Sb2Te5 thin films has been measured by time resolved reflectivity. An enhancement of the crystallization process occurred in the implanted samples. Raman scattering analysis was used to correlate the stability of the amorphous phase to its structure. The variation of the Raman signal after ion irradiation is consistent with a reduction in Ge–Te tetrahedral bonds, characteristic of the Ge coordination in amorphous Ge2Sb2Te5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
38
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 11 publications
4
38
0
1
Order By: Relevance
“…Therefore, appropriately reduced laser intensity and long acquisition time have been used to minimize any beam-induced crystallization. The main features of the obtained Raman spectra of amorphous GST-225 thin film are consistent with the spectra reported earlier for this material [38][39][40][41]. The broad bands with maxima at~80-90 cm -1 , ~125-135 cm -1 , ~145-155 cm -1 and~160-165 cm -1 can be distinguished readily (Fig.…”
Section: Page 14 Of 35supporting
confidence: 89%
See 1 more Smart Citation
“…Therefore, appropriately reduced laser intensity and long acquisition time have been used to minimize any beam-induced crystallization. The main features of the obtained Raman spectra of amorphous GST-225 thin film are consistent with the spectra reported earlier for this material [38][39][40][41]. The broad bands with maxima at~80-90 cm -1 , ~125-135 cm -1 , ~145-155 cm -1 and~160-165 cm -1 can be distinguished readily (Fig.…”
Section: Page 14 Of 35supporting
confidence: 89%
“…The first band (~80-90 cm -1 ) is observed usually in a singlecrystal -GeTe, and can be attributed to  3 (E) mode of rhombohedrally deformed rocksalt structure [42] and bending modes of GeTe 4 tetrahedra [40]. The second feature in the Raman spectra of the amorphous GST-225 film is a band peaking at ~125-135 cm -1 , which is connected with A 1 mode of corner-shared GeTe 4 tetrahedra and lighter Ge 2 Te 3 complexes [40,41]. The band at ~145-155 cm -1 is either associated with a stretching mode of SbTe 3 pyramids (comparing with Raman spectra of Sb 2 Te 3 [40]) or with the defective octahedral coordination of Sb atoms [38].…”
Section: Page 14 Of 35mentioning
confidence: 93%
“…4,6 Similar differences in the Raman spectra between unmodified and modified areas were observed on 70 nm and 2000 nm thick Ge 2 Sb 2 Te 5 films. Moreover, the Raman spectrum obtained on the modified area after exposure to the higher laser intensity, also shown in Fig.…”
supporting
confidence: 55%
“…Despite the long-established technological applications of chalcogenide films in optical data storage devices and the high level reached in the development of PCRAM, the phase change process of such compounds is still the object of intense theoretical and experimental investigations. These include the study of the atomic bonds rearrangement upon phase transition, using, e.g., Raman scattering spectroscopy measurements, which are very sensitive to the lattice vibrations that reflect the local symmetry of the material, [3][4][5][6] and the investigation on the structural changes induced by hydrostatic pressure. 7,8 On the other hand, alternative processes for the writing and reading of information that would allow higher storage density and overcome, for instance, the limits imposed by diffraction of laser impulse in optical storage devices are sought.…”
mentioning
confidence: 99%
“…This amorphous instability has not been yet understood and it has been explained by considering stress release (Pirovano et al 2004, Boniardi et al 2009), decrease of defect density (Ielmini, 2008), shift of the Fermi level or increase of the band gap (Pirovano et al, 2004). Indeed, it has been shown that amorphous phase change materials can have very different properties depending on the way they are produced (melt quenching, room temperature deposition or ion implantation) and on their thermal history (Lee et al, 2009, De Bastiani et al, 2008). …”
Section: Phase Change Memorymentioning
confidence: 99%